Melayu pesisir dan Batak pegunungan : orientasi nilai budaya - Simanjuntak, Bungaran Antonius, 1941- (Jakarta : Yayasan Obor Indonesia, 2010)
Social life and culture of Malay people in coastal areas of Sumatera and Batak Toba people in mountaineous areas of Sumatera.
Includes bibliographical references (p. 174-175).
Keywords: Malays (Asian people) -- Indonesia -- Sumatra -- Social life and customs; Toba-Batak (Indonesian people) -- Social life and customs; Sumatera Utara (Indonesia) -- Civilization